Kebijakan hutang perusahaan manufaktur di Indonesia - Hadi - Surento; Ika Rosyada Fitriati (Universitas Darussalam Gontor, 2020)
The purpose of this paper is to explore the most significant determinant of debt policy on manufacturing firm in Indonesia. This paper carries out a panel data analysis of 318 observations from 106 listed manufacturing firms on the Indonesia Stock Exchange over period 2016-2018. Multiple regression model and correlation matrix have been used as statistical tools to investigate the most significant determinants of debt policy on manufacturing firm in Indonesia. The results of this research shows that there is a significant negative effect of liquidity and profitability on debt policy, while the asset structure and firm size have a significant positive effect on debt policy.